Case Report: Extraction of a stylet-driven lead for left bundle branch area pacing >2 years after implantation - Romic, Ivana Grgic; Bastiancic, Ana Lanca; Zidan, David; Mavric, Mate; Brusich, Sandro (Frontiers in Cardiovascular Medicine, 2024)
Left bundle branch pacing has recently emerged as a significant alternative to right ventricular pacing. The rate of implanted stylet-driven septal leads is expected to increase substantially in the coming years, along with the need to manage long-term complications. Experience in extracting these leads is currently very limited, however the number of complex extractions is anticipated to grow in the future.We report a complex case involving the extraction of a long-dwelling Solia lead used for left bundle branch pacing in a 21-year-old man. The lead was extracted through the implant vein 27 months after implantation, using a methodology that involved a locking stylet and a compression coil. The new lead insertion was challenging due to venous occlusion, but after successful venoplasty, the His lead was successfully implanted. The postoperative course was uneventful, demonstrating the feasibility of extraction without complications.